Efek Pemberian Jus Bayam Merah Terhadap Peningkatan Kadar Hemoglobin Remaja Putri di MA Plus Sunan Drajat 7 Kecamatan Palang - Fitria Afifatussholihah; Dian Ayu Ainun Nafies (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Iron deficiency anemia represents a significant health burden among the female adolescent demographic, manifesting through multifaceted implications for physical well-being, cognitive function, and developmental processes. Clinical presentations commonly include persistent fatigue, diminished concentration capacity, and disruptions to normal growth patterns. Epidemiological data from Tuban Regency in 2023 revealed a concerning prevalence rate of 40.8% among adolescent girls, underscoring the critical requirement for effective intervention strategies. Dietary modification through consumption of iron-rich food sources emerges as a viable non-pharmacological approach, with Amaranthus dubius (red spinach) presenting particular promise due to its dual composition of bioavailable iron and vitamin C, the latter serving as a crucial cofactor in hemoglobin synthesis. This investigation employed a true experimental methodology incorporating pre-test and post-test measurements to examine the efficacy of red spinach juice supplementation on hemoglobin parameters. The study cohort comprised 30 anemic adolescent females from MA Plus Sunan Drajat 7 in Palang District, systematically allocated into intervention and control groups. Statistical evaluation using One Way Anova and Paired T-test procedures demonstrated that while the intervention did not produce statistically significant hemoglobin elevation across the entire sample, observable upward trends manifested within specific individual cases. These findings imply that red spinach juice may possess potential as an auxiliary nutritional intervention for hemoglobin enhancement in anemic adolescent girls, though its therapeutic application warrants further substantiation through expanded research parameters.